Natural Resource Endowments, Governance, and the Domestic Revenue Effort : Evidence from a Panel of Countries - Thornton, John (IMF Working Papers; Working Paper, 2008)
The recent development literature stresses that countries that receive large revenues from natural resource endowments typically raise less revenue from domestic taxation, and that this creates governance problems because the lower domestic tax effort reduces the incentive for the public scrutiny of government. Our results from a panel of 30 hydrocarbon producing countries indicate that the offset between hydrocarbon revenues and revenues from other domestic sources is about 20 percent but that it is invariant to governance indicators.